Duration of medical home participation and quality of care for patients with chronic conditions. (17th August 2021) - Swietek, Karen E.; Domino, Marisa Elena; Grove, Lexie R.; Beadles, Chris; Ellis, Alan R.; Farley, Joel F.; Jackson, Carlos; Lichstein, Jesse C.; DuBard, C. Annette
Abstract: Objective: To examine whether the length of participation in a patient‐centered medical home (PCMH), an evidence‐based practice, leads to higher quality care for Medicaid enrollees with multiple co‐morbid chronic conditions and major depressive disorder (MDD). Data Sources: This analysis uses a unique data source that links North Carolina Medicaid claims and enrollment data with other administrative data including electronic records of state‐funded mental health services, a state psychiatric hospital utilization database, and electronic records from a five‐county behavioral health carve‐out program. Study Design: This retrospective cohort study uses generalized estimating equations (GEEs) on person‐year‐level observations to examine the association between the duration of PCMH participation and measures of guideline‐concordant care, including the receipt of minimally adequate care for MDD, defined as 6 months of antidepressant use or eight psychotherapy visits each year. Data Collection/Extraction Methods: Adults with two or more chronic conditions reflected in administrative data, including MDD. Principal Findings: We found a 1.7 percentage point increase in the likelihood of receiving guideline‐concordant care at 4 months of PCMH participation, as compared to newly enrolled individuals with a single month of participation ( p  < 0.05). This effect increased with each additional month of PCMH participation; 12 months of participation was associated with a 19.1 percentage point increase in the likelihood of receiving guideline‐concordant care over a single month of participation ( p  < 0.01). Conclusions: The PCMH model is associated with higher quality of care for patients with multiple chronic conditions and MDD over time, and these benefits increase the longer a patient is enrolled. Providers and policy makers should consider the positive effect of increased contact with PCMHs when designing and evaluating initiatives to improve care for this population.